Fragmented QRS as a candidate marker for left ventricular nonrecovery in patients with peripartum cardiomyopathy - Tekin Tak, Bahar (Ann Noninvasive Electrocardiol, 2019)
BACKGROUND: Fragmented QRS (fQRS) complex, with various morphology, has been recently described as a diagnostic criterion of several cardiac diseases. However, there are little data regarding the prognostic role of fQRS in peripartum cardiomyopathy (PPCM) patients. We aimed to investigate the effect of fQRS on predicting left ventricular (LV) nonrecovery in patients with peripartum cardiomyopathy (PPCM). METHODS: Ninety patients (mean age: 34.7 ± 6.5 years) with the diagnosis of PPCM were analyzed retrospectively. The median follow‐up period of was 67.0 (12.0–192.0) months. Fragmented QRS was defined as the presence of various RSR’ patterns (QRS duration < 120 ms) with or without Q wave, which include an additional R wave (R’ prime) or notching of the R wave or S wave, or the presence of more than one R' (fragmentation) without typical bundle branch block. Recovery of LV function was defined as the presence of LV ejection fraction (EF) >45%. RESULTS: Of the patients, 54 (60%) did not recover LV function at the last follow‐up visit (nonrecovery group), while 36 of the patients (40%) exhibited LV recovery (recovery group). LV ejection fraction (EF) and fQRS were identified as independent predictors of LV nonrecovery in patients with PPCM (odds ratio OR: 5.546, 95% confidence interval CI: 0.792–0.979, p = .019 and OR: 5.986, 95% CI: 1.313–11.787, p = .014, respectively). CONCLUSION: Our data firstly indicated that presence of fQRS was a significant predictor of LV nonrecovery in patients with PPCM. The fQRS might assist in identifying high‐risk patients.